Sustainable development discourse in Smart Specialization Strategies - Polido, Alexandra (2020)
Smart Specialization Strategies have been used to implement European Union Cohesion Policy in recent years, aiming to achieve economic, social and territorial development by reducing disparities between regions. The European Union often declares an alignment between Cohesion Policy, Smart Specialization Strategies and the United Nations Agenda 2030. However, and despite the recurrent Sustainable Development discourse present in the European political agenda, it is not evident that Smart Specialization Strategies integrate Sustainable Development goals and practices. Hence, this paper aims to explore and discuss the degree of embeddedness of the Sustainable Development discourse in the Research and Innovation Strategies for Smart Specialization, using the Portuguese Centro Region as an exploratory study. In this research a content analysis of the Centro Region Smart Specialization Strategy was used for data collection and analysis, framed by the 17 goals of Agenda 2030 and their targets. Results show a good embeddedness of the overall goals of Agenda 2030, but a lower integration of the targets, suggesting that this strategy needs to be revisited to further integrate Agenda 2030. Moreover, the Centro Smart Specialization Strategy has a strong alignment with the goals related with economic and environmental issues, almost disregarding social aspects. These findings are amplified by the fact that this strategy is mainly being implemented through projects financed under the economy pillar. Finally, there is evidence about the need of developing regional innovation policies towards sustainable development from the regional to the national level. Overall, it is critical to enlarge the debate on how Smart Specialization Strategies can be an effective engine for a new development trajectory for European regions assuming the Agenda 2030 as a framework for the necessary change.